2016
DOI: 10.3998/mjm.13761231.0001.111
|View full text |Cite
|
Sign up to set email alerts
|

Relating Connectivity and Graph Analysis to Cognitive Function in Alzheimer’s Disease

Abstract: As a mathematical tool, graph analysis provides a way to understand changes in the brains of individuals with Alzheimer's disease and its associated devastating cognitive decline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…In general, graph theory in brain research presents "a network as a set of nodes, which are the components of a system (represented in the brain network perspective as a region of interest -ROI, and a number of edges, representing the connection (functional connectivity -FC) between each pair of nodes" (Sanz-Arigita et al 2010;Eid and Saleh 2013;Gits 2016). Several neuroimaging tools (e.g., MRI, EEG, etc) have been extensively used in order to extract different network properties.…”
Section: {Figure 1 About Here}mentioning
confidence: 99%
“…In general, graph theory in brain research presents "a network as a set of nodes, which are the components of a system (represented in the brain network perspective as a region of interest -ROI, and a number of edges, representing the connection (functional connectivity -FC) between each pair of nodes" (Sanz-Arigita et al 2010;Eid and Saleh 2013;Gits 2016). Several neuroimaging tools (e.g., MRI, EEG, etc) have been extensively used in order to extract different network properties.…”
Section: {Figure 1 About Here}mentioning
confidence: 99%
“…While, a volume-based morphological study has demonstrated that patients with mild cognitive impairment and AD could retain their hub regions in the frontal lobe but not in the temporal lobe (Yao et al, 2010). Furthermore, the graph-based analysis provides an approach to explore the relationship between network properties and cognitive functioning, which could help researchers to obtain more accurate predictions and diagnoses of AD (Gits, 2016). Such decreased functional connectivity of DMN is found related to the declined cognitive functioning (Binnewijzend et al, 2012), and altered path length of morphological networks in the medial posterior cortex showed the strong relationship with cognitive disruption (Tijms et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey by Gits ( 2016 ) of studies investigating graph properties in AD reveals no clear and systematic differences between heath conditions. For example, the mean clustering coefficient was found to be both significantly smaller (Supekar et al, 2008 ) and larger (Zhao et al, 2012 ) in AD compared to the aged-matched control group.…”
Section: Resultsmentioning
confidence: 99%
“…Although many fMRI studies have investigated changes of functional activity in AD (for a review see Dennis and Thompson, 2014 ), there is no consensus about which information should be used. Such studies typically examine disrupted cortical connectivity, either locally, considering single brain areas (e.g., Dillen et al, 2017 ) and their embedding in the network, or globally, analyzing the entire constructed brain graph and the statistics of its graph properties (Gits, 2016 ).…”
Section: Introductionmentioning
confidence: 99%